USE OF PHOSPHORIC ACID AS BIOADSORBENT ACTIVATOR OF KETAPANG LEAVES (Terminalia sp.) TO REDUCE RHODAMINE B CONTAMINANTS - Nadya Hasna; Dedy Suprayogi; Abdul Hakim (Konversi, 2021)
Ketapang contains tannin and phenolic compounds which are known to absorb metals and pollutants in the air. The purpose of this study was to determine the effectiveness of the biadsorbent from ketapang leaves (Terminalia sp.) on the adsorption of Rhodamine B dye without activation and with activation by 10% phosphoric acid. The study began with testing the variation of mass, time, and concentration of Rhodamine B by ketapang leaves. Then the adsorption process was carried out using a batch system and the concentration of the filtrate was measured using a UV-Vis spectrophotometer. Followed by the isotherm analysis of Freundlich and Langmuir. The results showed that the bioadsorbent ability of ketapang leaves without activation or with activation by 10% H3PO4 in terms of mass variation, contact time, and Rhodamine B concentration were 300 mg, contact time was 90 & 120 minutes, and Rhodamine B concentration was 10 mg/l. - 30 mg/l. The maximum bioadsorbent capacity of ketapang leaves (Qm) without activation was 3.7037 mg/g, while that of ketapang leaves with phosphoric acid activation was 1.0673 mg/g. The adsorption model used by the ketapang leaf bioadsorbent is the Freundlich isotherm where the R2 value close to 1 is 0.9573.